2021
DOI: 10.3390/nano11123290
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Synthesis of Iron Oxide Nanoparticles Using Enterococcus faecalis: Adsorption of Hexavalent Chromium from Aqueous Solution and In Vitro Cytotoxicity Analysis

Abstract: The biological synthesis of nanoparticles is emerging as a potential method for nanoparticle synthesis due to its non-toxicity and simplicity. In the present study, a bacterium resistant to heavy metals was isolated from a metal-contaminated site and we aimed to report the synthesis of Fe3O4 nanoparticles via co-precipitation using bacterial exopolysaccharides (EPS) derived from Enterococcus faecalis_RMSN6 strains. A three-variable Box–Behnken design was used for determining the optimal conditions of the Fe3O4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 71 publications
2
7
0
Order By: Relevance
“…XRD analysis resulted that the distinct peaks were found at 26, 33, 35, 55 and 62 • accounting for crystal planes 012, 104, 113, 214 and 300, respectively. These characteristic peaks are in agreement with standard diffraction data JCPDS: 34-0665 of hematite and correspond to face-centered cubic (fcc) symmetry (Asuha et al, 2009;Samuel et al, 2021). In addition, earlier reports found that Fe3O4 nanoparticle crystallinity was not changed by the chitosan coating (Li et al, 2008).…”
Section: Discussionsupporting
confidence: 88%
“…XRD analysis resulted that the distinct peaks were found at 26, 33, 35, 55 and 62 • accounting for crystal planes 012, 104, 113, 214 and 300, respectively. These characteristic peaks are in agreement with standard diffraction data JCPDS: 34-0665 of hematite and correspond to face-centered cubic (fcc) symmetry (Asuha et al, 2009;Samuel et al, 2021). In addition, earlier reports found that Fe3O4 nanoparticle crystallinity was not changed by the chitosan coating (Li et al, 2008).…”
Section: Discussionsupporting
confidence: 88%
“…Iron oxides are a group of naturally occurring materials with immense potential within the biomedical area owing to the iron component, which is an essential element within the organism [ 1 ]. Among them, magnetite nanoparticles are the first generation of clinically approved nanomaterials that have been intensively used for their superparamagnetic properties in novel and efficient biomedical applications [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Besides the possibility to adsorb and immobilize large quantities of bioactive compounds [ 1 ], magnetite nanoparticles are widely known for their intrinsic antioxidant [ 10 ], antimicrobial [ 11 ], and anticancer [ 12 ] properties, which can be potentiated through hyperthermia effects [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Samuel et al . 12 developed simple one-pot method and promoted the biological synthesis of nanoparticles as a promising method for nanoparticle synthesis. They have developed a hybrid polymer composite of lithocholic acid (LCA), zinc pyrithione (Zn) and cinnamaldehyde (Cn) (named as LCA–Zn–Cn) which displays potent antibacterial/antibiofilm activity 13 .…”
Section: Introductionmentioning
confidence: 99%
“…They have developed a hybrid polymer composite of lithocholic acid (LCA), zinc pyrithione (Zn) and cinnamaldehyde (Cn) (named as LCA–Zn–Cn) which displays potent antibacterial/antibiofilm activity 13 . Moreover, they have biosynthesized iron oxide nanoparticle (Fe 3 O 4 NPs) and showed its dual benefits as effective adsorbent for removal of heavy metal ion from wastewater and as biomedical agents 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation